Radzenie sobie ze stresem wśród młodzieży wielkopolskiej – przegląd problemów i strategii - Skowrońska-Pućka, Agnieszka; Garbacik, Żaneta (Kultura-Społeczeństwo-Edukacja, 2025)
The article analyzes stress and coping strategies among young people in the context of contemporary challenges (pandemic, digital changes, war in Ukraine, educational and professional pressure). The aim was to: (1) identify the most common stressors, (2) verify their relationship with gender, (3) compare dis-positional and situational coping strategies with stress according to gender and age. The study covered 181 students aged 11–18 (79 girls, 102 boys) from the Wielkopolska Province. The JSR questionnaire by Juczyński and Ogińska-Bulik was used to measure three strategies (active coping, focusing on emotions, seeking support) in terms of disposition and situation. The most frequently reported stressors were peer and school difficulties; no significant gender differences were found in their frequency (girls tended to report peer problems more often). In coping strategies, girls more often than boys used emotion focus (dispositional and situational) and more often declared dispositional support seeking; no gender differ-ences were found in active coping. With age, the use of situational focus on emotions and active coping increased (slightly to moderately); the effect was more pronounced in girls. The relationship between the number of problems and strategies was weak. The differences obtained in terms of gender and age suggest the need to profile preventive and support measures (greater emphasis on emotion regulation and social support in girls and on developing a repertoire of strategies in younger students).